You are on page 1of 8

# Fall 2011 oering of

AMATH 250
Introduction to Dierential Equations
Professor: J. West
University of Waterloo
LaTeXer: M. L. Baker <http://lambertw.wordpress.com>
Updated: September 21, 2011
Contents
1 Introduction 2
1.1 Dimensions (units) of physical quantities . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 2
1.2 Principle of dimensional homogeneity . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 2
1.3 Separable rst-order DEs . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 3
1.4 First-order linear DEs . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 4
1.4.1 General procedure . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 4
1.5 More curve sketching (1.2.4), Undetermined coecients (1.2.5) . . . . . . . . . . . . . . . . . . . . . . . . . . . . 6
1.5.1 General procedure . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 6
1.6 Undetermined coecients . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 7
These notes are currently a work in progress, and as such may be incomplete or contain errors.
1
Assignments due every Tuesday, Box #6 (slot 8-12) (last name)
Oce hours: MWF 9:50 - 10:10, 11:30 - 12:00; F 14:45 - 16:00.
1 Introduction
Denition 1.1. A dierential equation is an equation involving an unknown function and its derivative(s).
Example 1.2.
dy
dx
= y(x).
Solution. Some solutions are y = 0, y = e
x
, y = 2e
x
. Hence the general solution is y = Ce
x
.
Example 1.3 (Skydiver DE). A skydiver with downward velocity v(t), where we use the convention that downward is positive.
The forces are gravity (F
g
= mg where m is mass in kg, and g is the acceleration due to gravity, that is 9.8 metres per second
squared).
Suppose air drag F
d
is proportional to the velocity, so F
d
= v. Newtons second law therefore says
d
dt
(mv) = mg v.
Assuming the mass is constant, this gives the skydiver DE:
m
dv
dt
= mg v.
Solution. Find v(t) given m, g, . We could divide by m:
dv
dt
= g

m
v.
The naive approach is to integrate to get
v(t) =
_
_
g

m
v
_
dt
but v is an unknown function. So lets look at some qualitative solutions:
1.1 Dimensions (units) of physical quantities
Basic units: M (mass), L (length), T (time). Others include current, temperature , and so on.
Example 1.4. We use square-bracket notation to denote the dimension of a quantity:
[v] =
L
T
, [acceleration] =
_
dv
dt
_
=
L
T
2
, [force] = [ma] = M
L
T
2
= MLT
2
, [energy] = [mgh] = ML
2
T
2
.
1.2 Principle of dimensional homogeneity
Can only add or subtract quantities with the same dimensions.
3 kg + 4
m
s
is meaningless
but
3 kg + 4 g = 3.004 kg.
Example 1.5. Find [] in the Skydiver DE. We can set
[mg] = [v]

ML
T
2
= []
L
T
[] =
M
T
.
2
Example 1.6. What is [] if e
t
appears somewhere? (t is time). Well, look at the Taylor expansion
e
t
= 1 + (t) +
(t)
2
2
+. . .
hence obtain
[t] = 1 [] =
1
T
.
1.3 Separable rst-order DEs
Standard form:
dy
dx
= f(x, y).
Separable DE:
dy
dx
= A(x)B(y).
Example 1.7. We have the following rules:

dy
dx
= xcos y is separable.

dy
dx
y = ye
x
is separable.
The Skydiver DE is separable.

dx
dt
= t +x is not separable.
Example 1.8. How to solve a separable DE: we divide by B(y) to obtain
1
B(y)
dy
dx
dx = A(x)
Integrate w.r.t. x:
_
1
B(y)
dy
dx
dx =
_
A(x) dx
Change of variables/substitution rule gives
_
1
B(y)
dy =
_
A(x) dx
Then solve for y. Check where B(y) = 0 separately.
Example 1.9. For
dy
dx
= 2xy, if y = 0, the DE is satised. This is called an equilibrium (constant) solution. If y = 0, then
_
dy
y
=
_
2xdx
which gives
ln|y| = x
2
+C
and hence
|y| = e
c
e
x
2
therefore y = ke
x
2
where k = 0. This can be checked just by substituting back into the DE.
Example 1.10.
dy
dx
= y(y 2). The equilibrium solutions are y = 0 and y = 2. Otherwise,
_
1
y(y 2)
dy =
_
dx
therefore
_ _

1
2
y
+
1
2
y 2
_
dy = x +C
and so

1
2
ln|y| +
1
2
ln|y 2| = x +C
3
or
1
2
ln

y 2
y

= x +C
thus
y 2
y
= ke
2x
.
Solving,
y =
2
1 +ke
2x
.
Hence in conclusion the solutions are
y = 0 and y =
2
1 +ke
2x
, k R.
Example 1.11 (Newtons Law of Cooling). Consider the DE
dT
dt
= k(T T
A
)
where k is a proportionality constant, T is temperature of the object and T
A
is the (constant) ambient temperature. We have
an initial condition
T(0) = T
0
.
Solve:
_
dT
T T
A
=
_
k dt
and get
ln|T T
A
| = kt +C
1
hence
T T
A
= C
2
e
kt
Setting t = 0, we see that
C
2
= T
0
T
A
.
Therefore,
T(t) = T
A
+ (T
0
T
A
)e
kt
.
1.4 First-order linear DEs
General form is
dy
dx
+k(x)y = f(x).
Example 1.12.
dy
dx
+
1
x
y =
1
x
cos y, x > 0.
We get
x
dy
dx
+y = cos x
and hence
d
dx
(xy) = cos x = xy = sinx +C = y =
1
x
sinx +
C
x
.
1.4.1 General procedure
First multiply the general form equation by I(x) (integrating factor). We get
I
dy
dx
+I k(x)y = I f(x)
We would like this to become
d
dx
(I y) = I f(x).
i.e.
I
dy
dx
+
dI
dx
y = If(x)
4
The rst and third equations are equivalent if
dI
dx
= I k(x).
But this is a separable DE. Hence
_
dI
I
=
_
k(x) dx = ln|I| =
_
k(x) dx = I(x) = Ce
R
k(x) dx
.
We can set C = 1 for simplicity. Hence the formula for the integrating factor is
I(x) = e
R
k(x) dx
.
Then the DE becomes
d
dx
(I(x)y) = I(x)f(x).
Then integrate and solve for y.
Example 1.13. Consider
dy
dx
3
..
k(x)
y = 2e
x
..
f(x)
.
The integrating factor is e
R
3 dx
= e
3x
. The DE becomes
e
3x
dy
dx
3e
3x
y = 2e
x
e
3x
.
This becomes
d
dx
_
e
3x
y
_
= 2e
2x
.
Finally, integrate w.r.t. x to get
e
3x
y =
_
2e
2x
dx = e
x
+C.
Isolating for y, we get
y = e
x
+Ce
3x
.
Example 1.14. Consider
x
dy
dx
= 3y +x
5
e
x
, x > 0.
Dividing through by x and rearranging gives
dy
dx

3
x
y = x
4
e
x
which is in standard form. Integrating factor is
I(x) = e
R

3
x
dx
= e
3 ln x
= x
3
.
Multiply the DE by x
3
:
x
3
dy
dx
3x
4
y = xe
x
.
This becomes
d
dx
_
x
3
y
_
= xe
x
.
(Check). Integrate and get
x
3
y =
_
xe
x
dx = xe
x

_
(1)(e
x
) dx = xe
x
e
x
+C.
Hence
y = x
4
e
x
x
3
e
x
+Cx
3
.
Check that LHS=RHS in the DE.
5
Example 1.15 (Skydiver DE). Consider the (separable) DE
m
dv
dt
= mg v.
It is also linear:
dv
dt
+

m
v = g.
Integrating factor is
exp
__

m
dt
_
.
We get
e
(/m)t
dv
dt
+

m
e
(/m)t
v = ge
(/m)t
.
Becomes
d
dt
_
e
(/m)t
v
_
= ge
(/m)t
.
This gives
e
(/m)t
v =
mg

e
(/m)t
+C
hence
v(t) =
mg

+Ce
(/m)t
.
We perform the dimensional check:
_
mg

_
=
M
L
T
2
M
T
=
L
T
= velocity = [v].
Also
_

m
t
_
=
M
T
M
T = 1.
1.5 More curve sketching (1.2.4), Undetermined coecients (1.2.5)
1.5.1 General procedure
1. Equilibrium solutions
2. Exceptional solutions* (C = 0 usually)
3. Slope
4. Asymptotics*
5. Concavity
*: if solution known.
Example 1.16.
dy
dx
= 3y e
x
. Solve and sketch. Well, we get
dy
dx
3y = e
x
which is linear. Solve (exercise) to get y = Ce
3x
+
1
2
e
x
. To sketch:
Equilibrium solutions: set
dy
dx
= 0. Then 3y e
x
= 0 hence y =
1
3
e
x
, which is not constant. So there are no equilibrium
solutions.
Exceptional solutions: C = 0 yields y =
1
2
e
x
. Notice
u =
1
2
e
x
+Ce
3x
_
>
1
2
e
x
if C > 0
<
1
2
e
x
if C < 0
6
Slope:
dy
dx
= 3(y
1
3
e
x
)
_

_
> 0 if y >
1
3
e
x
= 0 if y =
1
3
e
x
< 0 if y <
1
3
e
x
Asymptotics:
1
2
e
x
+Ce
3x
_
Ce
3x
as x +

1
2
e
x
as x
Figure 1: See notebook 2011.09.21.1
Remark 1.17. Theoretical remark. First order DE:
dy
dx
= f(x, y). If f is C
1
then unique solution through each point.
Example 1.18. Pathological examples:

dy
dx
= y/x. This is solved by y = Cx (x = 0). [Diagram 2011.09.21.2]

dy
dx
= 3y
2/3
implies y = (x +c)
3
or y = 0. [Diagram 2011.09.21.3]
1.6 Undetermined coecients
Consider constant-coecient linear DE:
dy
dx
+ky = f(x).
Example 1.19. Find a particular solution to
dy
dx
+ 3y = x
2
+ 1.
Trial function: y = Ax
2
+Bx +C. Plug into DE:
(2Ax +B) + 3(Ax
2
+Bx +C) = x
2
+ 1.
We get
3Ax
2
+ (2A+ 3B)x + (B + 3C) = x
2
+ 1.
Equate coecients to get
3A = 1
2A+ 3B = 0
B + 3C = 1
A =
1
3
, B =
2
9
, C =
11
27
(exercise). So a particular solution
y
p
=
1
3
x
2

2
9
x +
11
27
.
7
To get the general solution, consider the homogeneous DE: (RHS = 0)
dy
dx
+ 3y = 0 = y
h
= Ce
3x
.
The above is called the homogeneous solution. Turns out that the general solution is obtained by
y(x) = y
h
(x) +y
p
(x).
8